2022
DOI: 10.3389/fcimb.2022.846828
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Affects Airway Epithelial Response and Barrier Function During Rhinovirus Infection

Abstract: Cystic fibrosis (CF) lung disease is aggravated by recurrent and ultimately chronic bacterial infections. One of the key pathogens in adult CF lung disease is P. aeruginosa (PA). In addition to bacteria, respiratory viral infections are suggested to trigger pulmonary exacerbations in CF. To date, little is known on how chronic infections with PA influence susceptibility and response to viral infection. We investigated the interactions between PA, human rhinovirus (HRV) and the airway epithelium in a model of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… Sörensen et al (2020) found that P. aeruginosa blocks the antiviral IFN signaling via LasR-dependent degradation of IFNλ by protease AprA. Endres et al (2022) also found that non-mucoid P. aeruginosa significantly controls the innate antiviral response, creating a favorable environment for RV infection. For example, IL-6 was almost completely degraded by bacterial protease, and the epithelial barrier function was also compromised.…”
Section: Major Human Infectious Diseases and Viral - Bacteria Co-infe...mentioning
confidence: 96%
“… Sörensen et al (2020) found that P. aeruginosa blocks the antiviral IFN signaling via LasR-dependent degradation of IFNλ by protease AprA. Endres et al (2022) also found that non-mucoid P. aeruginosa significantly controls the innate antiviral response, creating a favorable environment for RV infection. For example, IL-6 was almost completely degraded by bacterial protease, and the epithelial barrier function was also compromised.…”
Section: Major Human Infectious Diseases and Viral - Bacteria Co-infe...mentioning
confidence: 96%
“…For P. aeruginosa , one chronic ALI model was encountered where cells were repeatedly infected with bacteria over 16 days. To prevent high levels of cell death and bacterial overgrowth, the cell layers were washed daily, tobramycin was added to the cell–bacteria culture, and infectious doses of P. aeruginosa were kept low (MOI of 0.0025) (Endres et al 2022 ). Several ALI models for long-term M. pneumoniae infections have been described as well (Green et al 2009 , Thaikoottathil et al 2009 , Gross et al 2010 , Prince et al 2018 ).…”
Section: Initiation Of Bacterial Infectionmentioning
confidence: 99%
“…Adult human lung disease inflicts a large socio-economic burden and is a leading cause of morbidity and mortality worldwide (Refs 20 , 21 , 22 , 23 ). This includes acute lung disease in response to viral (e.g., influenza, rhinovirus (RV), SARS-CoV-2) or bacterial (e.g., Streptococcus, Haemophilus, Pseudomonas) infections and chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD), asthma, idiopathic pulmonary fibrosis (IPF), pulmonary arterial hypertension (PAH) (Refs 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ). Many of these diseases have mortality rates comparable to most types of lung cancer (Ref.…”
Section: Introductionmentioning
confidence: 99%